The Strange Death of the Realm of New Zealand: The Implications of a New Zealand Republic for the Cook Islands and Niue - Townend, Andrew (Victoria University of Wellington Law Review, 2003)
The Cook Islands and Niue are self-governing States within the Realm of New Zealand, freely associated with New Zealand and linked by a shared Head of State: the Sovereign in right of New Zealand. If New Zealand were to become a republic, it is likely that the constitutional link would be broken. The other aspects of the relationships of free association would not necessarily be affected, though their entrenched status in Cook Islands and Niue law could render difficult the technical amendments required to accommodate a republican New Zealand. A Realm of New Zealand of which New Zealand was no longer a part could also live on, with only minor amendment to the laws of the Cook Islands and Niue. But it would be neither desirable nor appropriate for current constitutional arrangements to continue. New Zealand’s becoming a republic would ultimately provoke fundamental constitutional change in the Cook Islands and Niue, mostly likely resulting in their becoming self-governing realms or republics in free association with New Zealand.